Perancangan Aplikasi Absensi Karyawan Berbasis Web pada Perusahaan PDAM Tirtanadi Sumatera Utara - Khaidir Hanafi; Abdul Halim Hasugian (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
The employee attendance system is a crucial component of human resource management, particularly for performance evaluation, salary calculation, and discipline monitoring. PDAM Tirtanadi North Sumatra still employs a manual attendance system, which is considered inefficient, prone to errors, and slows down administrative processes. This study aims to develop a web-based attendance application to improve the accuracy and efficiency of employee attendance data management. The research method uses software engineering with the System Development Life Cycle (SDLC) model based on the waterfall approach. Data collection was conducted through observation, interviews with relevant stakeholders, and literature review. The application is designed with several key features, including user authentication, digital attendance recording, employee data management, attendance recap, and report generation in PDF formats. Testing results show that the application operates according to system requirements and positively impacts the efficiency of the attendance process. The implementation of this application is expected to accelerate administrative procedures, enhance accountability, and provide a more accurate data foundation for analysis and managerial decision-making.